Navigating barren land. - Xie, Jane Zhen. (2009)
The adoption scene in Singapore is one that is unfamiliar to many. Singapore has been tightening the adoption process as it inches towards international practices, with new regulations introduced over the past few years. Meanwhile, there are still grey areas where the rules are not yet defined, such as the rules for the adoption agencies. How do the checks, or the lack of, affect the parties involved -- adoptive parents, social workers and the adoption agencies?